2018
DOI: 10.1186/s12902-018-0314-7
|View full text |Cite
|
Sign up to set email alerts
|

Low vitamin D levels are associated with cognitive impairment in patients with Hashimoto thyroiditis

Abstract: BackgroundCognitive impairment is commonly observed in patients with Hashimoto thyroiditis (HT). Low levels of vitamin D have been correlated with cognitive impairment in non-HT population. We examined the association of vitamin D levels with cognitive impairment in patients with HT.MethodsWe recruited 194 patients with HT and 200 healthy volunteers. Levels of serum 25-hydroxyvitamin D (25(OH)D) were measured using a competitive protein-binding assay. Cognitive funtion was assessed using Montreal Cognitive Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The clinical manifestations of autoimmune thyroiditis are not specific and are often low. However, many patients report numerous subjective complaints that have a significant impact on their quality of life 5 , 7 . In The Colorado Thyroid Disease Prevalence Study conducted in 2000, 18,750 people with compensated thyroid function were identified among 25,000 people in the general population, 114 patients with overt hypothyroidism and over 2300 patients with subclinical hypothyroidism 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical manifestations of autoimmune thyroiditis are not specific and are often low. However, many patients report numerous subjective complaints that have a significant impact on their quality of life 5 , 7 . In The Colorado Thyroid Disease Prevalence Study conducted in 2000, 18,750 people with compensated thyroid function were identified among 25,000 people in the general population, 114 patients with overt hypothyroidism and over 2300 patients with subclinical hypothyroidism 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Subclinical hypothyroidism may have a similar but more subtle effect on cognitive function 6 . However, there are few reports on cognitive disorders in patients with HT with compensated thyroid function, in whom difficulties with memory, focusing attention, or slowing down of thinking are often observed 7 , 8 . The cause of these symptoms has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GO enrichment analysis suggested that circRNAs are involved in a variety of biological processes, such as vitamin D receptor and MAPK binding. In addition, it has been reported that low levels of vitamin D may be involved in the occurrence of HT 30, 31, 32. It has also been suggested that MRP14 takes part in the pathogenetic process of HT through regulating the MAPK signal pathway 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a single type of collateral circulation: anterior communicating artery (AcoA), posterior communicating artery (PcoA), or ophthalmic artery (OA) confirmed by DSA were selected. The exclusion criteria included: 1) dementia (Montreal Cognitive Assessment < 26) [14]; 2) disturbance of consciousness; 3) transient ischemic attack (TIA); 4) MRI showing cerebral infarction or other pathological brain diseases, such as hemorrhages, tumors, aneurysms and vascular anomalies; 5) inadequate temporal window in TCD examination; 6) concomitant stenosis in other arteries; or 7) color blindness or color weakness. According to the type of collateral circulation, patients were classified into three groups: AcoA group, PcoA group, and OA group.…”
Section: Methodsmentioning
confidence: 99%